(3cfR GdYdhe hGdOQ GdefXhe aj MbGFb Yde GdTQjYI hhbGFY Yde GdWHjYIs - (3LeGd GdOjf eMeO Hf Ydj (B((3Gh YHO Gddg(B) (3Hf JheQJ GdeUehOj GdHQHQj GddbH HGdegOj, GdegOj,J (B524 (3g` s
(3ChdgG (B:s
(3CeG HYO aEf dcd YGde efgGL , jfgL ajg ef GdYdhe Edi GdBge aGdBge s
(3BNQgG (B:s
(3aGYed Hg UMjM eLQH (B" (3hGddg CYde hCMce Je GdcJGH s
(3Vef eLehY s
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3HQhcdeGf edMb (B- (3GdLRA (B1 - (3U (B424 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B4 - (3bSe eYGQa YGeg (B- (3U (B91 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
Keywords: (3GdeYGQa GdYGeIs